2018
DOI: 10.3389/fncom.2018.00036
|View full text |Cite
|
Sign up to set email alerts
|

Compensation for Traveling Wave Delay Through Selection of Dendritic Delays Using Spike-Timing-Dependent Plasticity in a Model of the Auditory Brainstem

Abstract: Asynchrony among synaptic inputs may prevent a neuron from responding to behaviorally relevant sensory stimuli. For example, “octopus cells” are monaural neurons in the auditory brainstem of mammals that receive input from auditory nerve fibers (ANFs) representing a broad band of sound frequencies. Octopus cells are known to respond with finely timed action potentials at the onset of sounds despite the fact that due to the traveling wave delay in the cochlea, synaptic input from the auditory nerve is temporall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 27 publications
(41 reference statements)
0
14
0
Order By: Relevance
“…Octopus cells are topologically arranged in frequency-ordered laminae and locally wired to bundles of ANFs. The wiring patterns' scheme constitutes their temporal receptive fields (TRFs) (Oertel et al, 2017;Spencer et al, 2018). Octopus cells latency-phase rectify space-time trajectories in their TRFs (Golding and Oertel, 2012;McGinley et al, 2012).…”
Section: Methodsmentioning
confidence: 99%
“…Octopus cells are topologically arranged in frequency-ordered laminae and locally wired to bundles of ANFs. The wiring patterns' scheme constitutes their temporal receptive fields (TRFs) (Oertel et al, 2017;Spencer et al, 2018). Octopus cells latency-phase rectify space-time trajectories in their TRFs (Golding and Oertel, 2012;McGinley et al, 2012).…”
Section: Methodsmentioning
confidence: 99%
“…We model onset behaviour abstractly as the weighted difference of two low-pass filtered signals (with different time constants). This can be interpreted either as two precisely timed excitatory/inhibitory pathways, or in a similar way to the octopus cell model of Spencer et al (2012Spencer et al ( , 2018 and Ferragamo and Oertel (2002). Their model uses a spike threshold on the rate of change of the membrane potential Brette, 2010, 2011), which we reformulated in terms of firing rates (see Methods and Appendix).…”
Section: Onset and Adaptation Mechanisms Can Explain Rising Slope Prementioning
confidence: 99%
“…The compression and gain mechanisms did not contribute substantially ( Figure 3A). We investigated the octopus cell model discussed earlier (Ferragamo and Oertel, 2002;Spencer et al, 2012Spencer et al, , 2018 and found that it could provide a good fit only if adaptation was present alongside the onset mechanism ( Figure 3AD). For model variants including the onset mechanism, the positive or excitatory time constant τ e must be small (Figures 2A and 4B), and the negative or inhibitory time constant τ i must be larger than τ e ( Figure 3CD, τ e versus τ i ).…”
Section: Mechanisms Are Highly Robustmentioning
confidence: 99%
See 2 more Smart Citations